2006
DOI: 10.1074/jbc.m600236200
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Microglial CD11b Expression by Nitric Oxide

Abstract: Increased expression of CD11b, the ␤-integrin marker of microglia, represents microglial activation during neurodegenerative inflammation. However, the molecular mechanism behind increased microglial CD11b expression is poorly understood. The present study was undertaken to explore the role of nitric oxide (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
171
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 184 publications
(177 citation statements)
references
References 44 publications
6
171
0
Order By: Relevance
“…Markey et al (23) (25,26), which have been shown to play an important role in the loss of dopaminergic neurons in MPTPintoxicated mice and PD patients (8)(9)(10)(11)(12). Recently, we have demonstrated that, once NO is produced via NF-B-dependent pathway, it up-regulates the expression of GFAP in astroglia and the expression of CD11b in microglia through NF-B-independent but guanylate cyclase-cGMP-protein kinase G-dependent pathways (27,28). Because glial production of proinflammatory molecules and gliosis are important features of PD pathology, it appears that NF-B activation regulates these pathological features either directly or indirectly and that NBD peptide protects dopaminergic neurons in MPTP-intoxicated mice via suppression of NF-Bdependent pathological steps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Markey et al (23) (25,26), which have been shown to play an important role in the loss of dopaminergic neurons in MPTPintoxicated mice and PD patients (8)(9)(10)(11)(12). Recently, we have demonstrated that, once NO is produced via NF-B-dependent pathway, it up-regulates the expression of GFAP in astroglia and the expression of CD11b in microglia through NF-B-independent but guanylate cyclase-cGMP-protein kinase G-dependent pathways (27,28). Because glial production of proinflammatory molecules and gliosis are important features of PD pathology, it appears that NF-B activation regulates these pathological features either directly or indirectly and that NBD peptide protects dopaminergic neurons in MPTP-intoxicated mice via suppression of NF-Bdependent pathological steps.…”
Section: Discussionmentioning
confidence: 99%
“…After pH adjusting and filtration, 10 l of supernatant was injected onto a Eicompak SC-3ODS column (HPLC-ECD System EiCOM-HTEC-500 from JM Science) and analyzed as described in ref. 28.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is not clear whether this blockade is caused by intrinsic effects of the drug on microglia or by an inhibitory action upstream on signaling mechanisms at the origin of microglia activation. Microglia activation can be triggered by numerous stimuli such as glutamate (Tikka and Koistinaho, 2001), ATP (Ferrari et al, 1997), or nitric oxide (Roy et al, 2006), which are released by injured neurons (Minc-Golomb et al, 1996). In addition, IL-6-deficient mice exhibit altered microglia activation (Klein et al, 1997;Galiano et al, 2001) and neuronal overexpression of IL-6 potentiates glia activation (Fattori et al, 1995), further suggesting a role for IL-6 in microglial activation.…”
Section: Cytokines Neuronal and Glial Markers In Sensory Gangliamentioning
confidence: 99%
“…Although GFAP is a marker of astrocytes, microglia are identified by CD11b. Similarly, the expression of GFAP increases during activation of astrocytes and astrogliosis, whereas the expression of CD11b goes up during activation of microglia and microgliosis (31,32). Therefore, to understand whether the effect of gem was specific for oligodendrocytes, we analyzed the mRNA expression of GFAP and CD11b in gem-treated mixed glial cells.…”
Section: Effect Of Gem On the Expression Of Myelin Genes In Human Fetmentioning
confidence: 99%